MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH DAN TANTANGANNYA (STUDI KASUS TK ISLAM TUNTANG) - Zulfiana; Noor Miyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to find out how School-Based Quality Improvement Management works by looking at educational input, educational processes and educational output. This research was conducted at the Tuntang Islamic Kindergarten which received category "A" accreditation from the National PAUD Accreditation Board (BAN). The research method used is a qualitative research method with a case study approach. Data collection techniques were carried out through observation, interviews and documentation studies. Research subjects or informants are school principals and teachers. The results found and presented from this research are: 1) Tuntang Islamic Kindergarten educational input, including human resources, other resources, institutional software, and school expectations; 2) educational processes related to the teaching and learning process and the process of managing teaching staff; 3) educational output that is in accordance with the objectives of the Tuntang Islamic Kindergarten. The researcher concluded that the three characteristics of educational quality have reached the standard of achieving educational quality.